"At First It Wasn't so Bad": How Adults Aged 60 and Older Feel About Social Distancing During COVID-19. Issue 3 (3rd April 2023) - Emerson, Kerstin G.; Kim, Deborah; Mois, George; Beer, Jenay M.
ABSTRACT: We conducted an exploratory study to describe the emotional experience of adults aged 60 and older in the United States practicing social distancing during COVID-19. The survey asked respondents how they were feeling during social distancing. Responses (n=673) were coded into segments by affect and then specific emotional states. A large portion of respondents reported negative emotions (e.g. anxiety, loneliness). A smaller portion reported positive emotions (e.g. optimism, gratitude). Younger respondents (aged 60-70) reported more feelings of anxiousness and fear compared to older respondents (71+). Older respondents were more likely to report negative feelings towards the government. For both age groups, female respondents were significantly more likely to report feeling afraid and having negative feelings about their own health. We conclude that many older adults are vulnerable to negative emotional outcomes during the pandemic. This highlights the importance of interventions targeting vulnerable older adults.